THE IMPLEMENTATION OF PROBLEM BASED LEARNING IN TEACHING DIRECTION - Tuzzahro, Ana Latifah (Politeknik Siber Cerdika Internasional, 2024)
The research focus in this research is, The implementation of Problem Based Learning In Teaching Direction At Junior State 1 Sumber, Students' perceptions of Problem Based Learning in Teaching Direction At Junior State 1 Sumber. The purpose of this research: To investigate the implementation of problem based learning in teaching direction at Junior State 1 Sumber, To investigate student's perception at the implementation of problem based learning at Junior State 1 Sumber. This research approach is a qualitative approach. This type of research is field research in the form of case study. Data collection techniques using observation, interviews, lesson plan and questionnaire for studen’t perception. While the data analysis uses the Miles and Huberman Models. The validity of the data used is source triangulation and technique triangulation. Research results from the Implementation Problem Based Learning in Teaching Direction At Junior State 1 Sumber Planning includes preparing learning tools and selecting learning materials, Implementation includes, conveying learning objectives, dividing groups, guiding discussions, presenting the results of discussions. And evaluate the results of the discussion, Students' of the learning by using a questionnaire.